Impact of handedness on electromyographic activity of hand muscles and nerve conduction velocity during mobile phone use in adolescents - Sami Elsaharty, Karim; Hamed Elmarakby, Shaimaa Mohamed; Nabil Alagamy, Nevein; Ibrahim, Maha G.; Abdelnabi Mousa, Nehad Mohamed; Hussien, Rana Nabil (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study investigated the impact of handedness on electromyographic (EMG) activity of hand muscles and nerve conduction velocity during smartphone use and compared the effects of left- and right-handedness on hand muscle activation and nerve conduction velocities. This interventional parallel study included 70 participants (35 left-handed, 35 right-handed) aged 12 to 14 years. EMG activity and nerve conduction velocities (radial, median, and ulnar nerves) were measured before and after 10 minutes of smartphone use. Muscle activation was assessed for the abductor pollicis longus (APL), extensor carpi radialis (ECR), flexor carpi ulnaris (FCU), and first dorsal interosseous muscles. Statistical analysis was performed using SPSS software, version 27. Left-handed participants exhibited significantly greater activation in all assessed muscles during smartphone use (p < 0.05). Specifically, the activation of the APL, ECR, FCU, and first dorsal interosseous muscles was higher in left-handed individuals. Sensory ulnar and median nerve conduction velocities were significantly higher in right-handed subjects during smartphone use (p < 0.05), while no significant differences were observed in motor nerve conduction velocities. The study demonstrates that handedness influences neuromuscular activity during smartphone use, with left-handed individuals showing greater muscle activation and right-handed individuals exhibiting higher sensory nerve conduction velocities.